The intermediate nebular phase of SN 2014J: onset of clumping as the source of recombination. Issue 2 (3rd April 2020) - Mazzali, P A; Bikmaev, I; Sunyaev, R; Ashall, C; Prentice, S; Tanaka, M; Irtuganov, E; Melnikov, S; Zhuchkov, R
ABSTRACT: At the age of about 1 yr, the spectra of most Type Ia supernovae (SNe Ia) are dominated by strong forbidden nebular emission lines of Fe ii and Fe iii . Later observations (at about 2 yr) of the nearby SN 2011fe showed an unexpected shift of ionization to Fe i and Fe ii . Spectra of the very nearby SN Ia 2014J at an intermediate phase (1–1.5 yr) that are presented here show a progressive decline of Fe iii emission, while Fe i is not yet strong. The decrease in ionization can be explained if the degree of clumping in the ejecta increases significantly at ∼1.5 yr, at least in the Fe-dominated zone. Models suggest that clumps remain coherent after about one year, behaving like shrapnel. The high density in the clumps, combined with the decreasing heating rate, would then cause recombination. These data may witness the phase of transition from relatively smooth ejecta to the very clumpy morphology that is typical of SN remnants. The origin of the increased clumping may be the development of local magnetic fields.